If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7(x-6)-3=4(x+7)
We move all terms to the left:
-7(x-6)-3-(4(x+7))=0
We multiply parentheses
-7x-(4(x+7))+42-3=0
We calculate terms in parentheses: -(4(x+7)), so:We add all the numbers together, and all the variables
4(x+7)
We multiply parentheses
4x+28
Back to the equation:
-(4x+28)
-7x-(4x+28)+39=0
We get rid of parentheses
-7x-4x-28+39=0
We add all the numbers together, and all the variables
-11x+11=0
We move all terms containing x to the left, all other terms to the right
-11x=-11
x=-11/-11
x=1
| 2/7y+5=-9 | | 27y+5=-9 | | 6.5x+2.5=74 | | 4p+24=1.6p+12 | | 10(x-8)-8=16x-118 | | 006x-0.18=0.12 | | 5(4y+22)=185 | | -3.1071=(x-69)/2.8 | | -4(x-9)+9x=6(x-3)+8 | | 3x-2x+4=40 | | 7x^2+4x=75 | | -3(x-1)+6=8(x-2) | | 15x-52=98 | | 3(e+9)=39 | | 15x-52=180 | | 3x^2-8-19=0 | | 15x-52=82 | | -3(x-1)+6=8(x—2) | | -6p-4=-2(-3p+2) | | 2x+15+4x=645 | | 2b2-b2=100 | | -6+2h=-4 | | 4x^2+2(x+5)=0 | | –x–20=–12 | | 2b^2-b^2=100 | | Y=3x+0-6 | | 4x^2+2(x+5=0 | | 6x-1+7x+13=180 | | 8x-x+9-1=7x-x+7 | | 1/9z=-8 | | (2d)-1=4 | | 2-2g=0 |